2016
DOI: 10.1007/s12560-016-9228-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Molecular Genotyping of Noroviruses in Market Oysters, Mussels, and Cockles in Bangkok, Thailand

Abstract: Noroviruses are the most common cause of acute gastroenteritis associated with bivalve shellfish consumption. This study aimed to detect and characterize noroviruses in three bivalve shellfish species: oysters (Saccostrea forskali), cockles (Anadara nodifera), and mussels (Perna viridis). The virus concentration procedure (adsorption-twice elution-extraction) and a molecular method were employed to identify noroviruses in shellfish. RT-nested PCR was able to detect known norovirus GII.4 of 8.8 × 10(-2) genome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 39 publications
0
10
1
1
Order By: Relevance
“…Norovirus RNA was detected in 68.7% of samples tested, comparable with the prevalence found in a previous survey carried out using the same methods on oysters from UK production areas (76.2%; Lowther et al 2012b ). The prevalence described here is considerably higher than recorded in surveys of norovirus in bivalve shellfish collected at the point-of-sale in some other countries, for example the United States (3.9%; Woods and Burkhardt 2010), France (9%; Schaeffer et al 2013 ) and Thailand (12.3%: Kittigul et al 2016 ); however, comparatively frequent detection of norovirus has been reported in shellfish from production areas in Ireland (37.1%; Flannery et al 2009 ), Italy (51.5%, Suffredini et al 2014 ) and Spain (52.4%; Polo et al 2015 ). Although the majority of samples were found to be positive, levels exceeding 100 norovirus copies/g were found in only a relatively small percentage of samples (9.7%).…”
Section: Discussioncontrasting
confidence: 53%
“…Norovirus RNA was detected in 68.7% of samples tested, comparable with the prevalence found in a previous survey carried out using the same methods on oysters from UK production areas (76.2%; Lowther et al 2012b ). The prevalence described here is considerably higher than recorded in surveys of norovirus in bivalve shellfish collected at the point-of-sale in some other countries, for example the United States (3.9%; Woods and Burkhardt 2010), France (9%; Schaeffer et al 2013 ) and Thailand (12.3%: Kittigul et al 2016 ); however, comparatively frequent detection of norovirus has been reported in shellfish from production areas in Ireland (37.1%; Flannery et al 2009 ), Italy (51.5%, Suffredini et al 2014 ) and Spain (52.4%; Polo et al 2015 ). Although the majority of samples were found to be positive, levels exceeding 100 norovirus copies/g were found in only a relatively small percentage of samples (9.7%).…”
Section: Discussioncontrasting
confidence: 53%
“…Genetic characterization of partial NoV capsid gene sequences demonstrated wide variety of NoV genotypes identified in bivalve shellfish. Among these, five different genotypes of NoV GI (GI.2, GI.3, GI.4, GI.5, and GI.9) and four different genotypes of NoV GII (GII.1, GII.2, GII.3, and GII.4) were detected . Most recently, detections of multiple NoV genogroups (GI, GII, and GIV) have been reported in oyster tissues from fresh markets in Bangkok from 2014 to 2016.…”
Section: Contaminations Of Nov and Sav In Food Supplies And Environmementioning
confidence: 99%
“…Among these, five different genotypes of NoV GI (GI.2, GI.3, GI.4, GI.5, and GI.9) and four different genotypes of NoV GII (GII.1, GII.2, GII.3, and GII.4) were detected. 57 Most recently, detections of multiple NoV genogroups (GI, GII, and GII, and GIV) were detected, these included 34.1% of GI, 10.5% of GII, 1.2% of mixed GI and GII, and 1.2% of GIV. For NoV GI genotype, only GI.2 was identified, while three GII, GII.4, GII.17, and GII.21 genotypes were identified.…”
Section: Contaminations Of Nov and Sav In Food Supplies And Environmentioning
confidence: 99%
“…GI HuNoVs strains have been more frequently encountered in oyster-related outbreaks, and noted to bio-accumulate in various oyster tissues (Le Guyader et al, 2012; Kittigul et al, 2016). GII HuNoVs strains have been also found in oyster tissues, but have been noted to bio-accumulate at very low levels (Wang et al, 2008b; McLeod et al, 2009; Le Guyader et al, 2012).…”
Section: Discussionmentioning
confidence: 99%